PHYSICS PERSPECTIVES ON HUMAN LOCOMOTION: INVESTIGATING THE MECHANICS OF WALKING PATTERNS - Ameen , Rayan Basheer M.; Mohammed , Dilveen W.; Bowen , James (Science Journal of University of Zakho, 2024)
This study investigated the gait metric differences between males and females aged 18 to 22. Our investigation revealed some significant changes in gait metrics between the two genders. Firstly, males exhibited greater leg and step lengths than females. Males exhibited wider strides, suggesting typical anthropometric variations. Except for BMI and cadence, males had more variation in practically every other gait metric, whereas females had more variability. There was a non-significant positive connection between BMI and gait metrics such as height, stride length, and step width, with BMI having a minor effect on those measures. Overall, both genders showed a distinct pattern of variability, revealing individual variances in gait analysis across the same genders. A direct correlation was observed between the Froude number and height, indicating that individuals with a higher Froude number exhibit a more dynamic and faster walking style. This phenomenon can be ascribed to the biomechanical superiority that taller individuals may possess, enabling them to generate longer strides and achieve higher speeds. A thorough study of walking speed and gait parameters revealed difficulty in finding the right balance between stability, efficiency, and speed in human movement. Understanding these connections will help people develop more efficient training programs, assistive technologies, and more efficient and safe walking in general.